Peluang dan Ancaman Strategi Pemasaran Syariah Biro Jasa Umroh (Studi Kasus di AET Travel PT Penjuru Wisata Negeri Sidoarjo). - Megawati, Rahayu; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2019)
The number of applicants jamaahUmrahin Indonesia, that is so much the main attraction for entrepreneurs the field of travel. Somany travel entrepreneurs who open a service bureau or the organizers of the pilgrimage. This research used a qualitative approach and is the type of field research. As a source of practical, this research was done at the travel organisers AET Travel PT. As a result, first, of the marketing strategies appliedin PT PenjuruWisataNegeriSidoarjo has fullfiled the marketing characteristics of Islam, namely to apply the principle of rabbaniyah, akhlakiyyah, realistic and humanistic. Second, the chance ownedPT Penjuru Wisata Negeri Sidoarjo is the high interest of Hajj and Umrah that is in East Java, an very strong religiosity, and condensed, as well as the existence of trust and cooperation with financial institutions.